Analysis of Bonjor Sugar Business Feasibility Study in Karyamukti Village (Case Study on Mr. Lukman’s MSMEs) - Bella Lutfiyya; Armaini Akhirson (Ilomata International Journal of Management, 2023)
Bonjor Sugar is one of the typical preparations from the Gunung Padang Cultural Heritage Site in Karyamukti Village, one of the managers of the Bonjor Sugar Business is Mr. Lukman. As a business that has been running for a long time, Mr. Lukman's business did not test the feasibility of the business he was running. There are several problems related to accessibility, technology, and limited knowledge of human resources. The purpose of this analysis is to test the feasibility of Mr. Lukman's Bonjor Sugar Business. This research uses a mixed or combination research method where data is obtained based on the results of interviews and observations. The results obtained are that there are several aspects that have not been fulfilled. Of the 7 aspects analyzed, only financial, economic and social aspects, as well as environmental aspects are considered feasible.